Niche markets ready for expansion - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Europeans, particularily northern Europeans, increasingly consume organic produce. These consumers place a high value on organic farm products (fresh or processed) because no chemicals are used in their production. For many Europeans, the organic...